PERANAN PERAWAT GIGI DALAM PEMELIHARAAN KESEHATAN GIGI DAN MULUT PADA ANAK BERKEBUTUHAN KHUSUS (DISABLED CHILDREN) - I Gede Surya Kencana (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2014)
Dental health is one of the most important things for growing children. However, in Indonesia, not many parents are concerned about the dental health of children, especially in children with special needs. Children with special needs are children who have mental disorders are like autism, Down syndrome and cerebral palsy,